Robust fault-tolerant control with dynamic event-triggered mechanism based on observer for nonlinear switched systems - Wang, Xiaohan; Fu, Xingjian (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
In this paper, a robust fault-tolerant control with a dynamic event-triggered mechanism based on the observer is proposed for a nonlinear switched system with faults, external disturbances, and uncertainties. A first-order filter is utilized to equate sensor faults to actuator faults, and the augmented system is constructed. An adaptive observer with H∞ performance is designed based on the augmented system. The condition that the state error and fault error of the adaptive observer are uniformly bounded is given. To save communication resources and reduce the transmission of unnecessary information, an improved dynamic event-triggered mechanism is designed by introducing a fixed threshold and defining a sampling error function based on the observed state and the actual state. This mechanism can further expand the triggering time interval and effectively avoid the Zeno behavior. According to the observed state and real-time fault estimation information at the triggering moment, a fault-tolerant controller for the switched system based on the dynamic event-triggered mechanism is proposed, and the conditions for asymptotic stability of the closed-loop system are provided. Finally, the validity of the proposed method is verified by application simulation for the variant aircraft switched system.